2013
DOI: 10.1039/c3np70038k
|View full text |Cite
|
Sign up to set email alerts
|

Catechin prodrugs and analogs: a new array of chemical entities with improved pharmacological and pharmacokinetic properties

Abstract: Extensive research on tea catechins, mainly (-)-epigallocatechin gallate, has shown numerous health promoting effects. However, various clinical studies demonstrated several issues associated with tea catechins which account for their poor systemic bioavailability. In order to improve pharmacological activity and bioavailability of natural tea catechins, two major strategies have been adopted to date which include synthesizing catechin analogs/prodrugs and the development of novel drug delivery systems. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 153 publications
(210 reference statements)
0
27
0
Order By: Relevance
“…31 In addition, these natural antioxidants possess the ability to detoxify enzyme components, such as GST. 15 The current reports further verify that the bioavailability issue of these compounds can be overcome by delivering these compounds via a topical route of drug administration. 15 The current reports further verify that the bioavailability issue of these compounds can be overcome by delivering these compounds via a topical route of drug administration.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…31 In addition, these natural antioxidants possess the ability to detoxify enzyme components, such as GST. 15 The current reports further verify that the bioavailability issue of these compounds can be overcome by delivering these compounds via a topical route of drug administration. 15 The current reports further verify that the bioavailability issue of these compounds can be overcome by delivering these compounds via a topical route of drug administration.…”
Section: Discussionmentioning
confidence: 54%
“…4 These polyphenols have been found to exert antioxidant, 5,6 anticancer, 7,8 antiviral, 9,10 antibacterial, 11,12 and anti-inflammatory 13,14 actions in both in vitro and in vivo models. 15 In our previous research, we found that a (+)-catechin rich aqueous extract of Acacia catechu shows chemopreventive effects against skin, 16 liver, 17 and breast cancers. 1).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…From a synthetic point of view, replacement of the bridging ester with other functionalities is more challenging than substitution at the peripheral phenolic hydroxyl groups (OR, Figure ). In addition, substitution at the epimerization‐susceptible 3‐position provides additional consideration . In this study, we devised a synthetic route to an amide analog of EGCG [EGCG‐Amide ( 3 ), Figure ], which showed preferential cytotoxicity toward triple‐negative breast cancer cell.…”
Section: Methodsmentioning
confidence: 99%
“…3 Not surprisingly, there have been significant activities toward the synthesis of these molecules and their derivatives to explore and improve the biological profiles. 4 A common feature of catechins is that they undergo oxidative oligomerization in vivo through the benzylic position of the C-ring and hence potential bioaccessibility of parent catechins is reduced. 3 Along this line, we hypothesize that with the congeneric 4-arylchroman-3-ols ( Figure 1) the relevant biological activities might not be compromised 5 and oxidative oligomerization might be suppressed.…”
Section: Introductionmentioning
confidence: 99%